2021
DOI: 10.1007/s40615-021-01100-w
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometer-Measured Physical Activity and Cardiometabolic Risk Factors by Race-Ethnicity: 2003–2006 NHANES

Abstract: Previous studies suggest that the magnitude of morbidity/mortality reduction may differ between race-ethnic groups despite equated dose of physical activity (PA). The purpose of this study was to compare the potential racial-ethnic differences in cardiometabolic risk factors (CMRF) across quartiles of accelerometer-derived total activity counts/day (TAC/d) among US adults. The final sample (n=4144) included adults who participated in the 2003-2006 National Health and Nutrition Examination Survey (NHANES). CMRF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Various electronic devices have emerged to provide accurate measurements of physical activity levels, one of which is the accelerometer 41 . Previous studies have used accelerometers to establish relationships with cardiometabolic risk factors 42 , 43 . The study by Silva et al 42 has sought to examine the combined association of different intensities of physical activity and sitting time with cardiometabolic risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Various electronic devices have emerged to provide accurate measurements of physical activity levels, one of which is the accelerometer 41 . Previous studies have used accelerometers to establish relationships with cardiometabolic risk factors 42 , 43 . The study by Silva et al 42 has sought to examine the combined association of different intensities of physical activity and sitting time with cardiometabolic risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Boyer's study revealed that similar levels of physical activity can reduce all-cause and diabetes-related mortality risk among non-Hispanic whites (and non-Hispanic blacks) but have no effect on Mexican Americans [30,31]. Boyer's study found significant racial-ethnic differences in several cardiometabolic risk factors among those who had similar levels of physical activity [32]. In addition, ethnicity can impact cortisol, β-endorphin, and allopregnanolone interactions with HPA axis functioning to influence the pain experience [33].…”
Section: Discussionmentioning
confidence: 99%